Pelatihan Teknik Budidaya Mencit Putih (Mus musculus L.) sebagai Peluang Usaha Kreatif kepada Siswa SMAN 5 Bukittinggi - Putra Santoso; Resti Rahayu; Robby Jannatan (Warta Pengabdian Andalas, 2020)
A marked increase in demand for white mice (Mus musclulus L., mammals) in the Indonesian market has been attributed to the price soar, while the availability of mice with a standardized quality remains very limited. Considering such condition, a business focusing on standardized farm of white mice should be actively socialized to younger people thereby elevating their enthusiasm in the entrepreneurship. This community service program aimed to provide insights as well as to train the basic skills in white mouse farming for students of the National High School Number 5 Bukittinggi. The program has been carried out for one day in the Biology Department, Andalas University with 45 participants. We deployed the lectures and hands-on practice on the aspects of white mouse farming. All participants have directly practiced various principle techniques in mice farming such as handling, sexing, mating, and raising brooders. This activity has increased the interest of the participants in such creative business. In the future, some efforts should be made to ensure the sustainability of the program by involving the participants from other schools, teachers and unemployed youth in West Sumatra.